Microplastics in Landfills: A Comprehensive Review on Occurrence, Characteristics and Pathways to the Aquatic Environment - Upadhyay, Kshitij; Bajpai, Samir (Nature environment and pollution technology, 2021)
Microplastics, a multi-dimensional environmental stressor group, capable of transboundary migration, are a threat to the global ecosystem. Transboundary migration of microplastics across all environmental matrices is known to originate from a multitude of sources and acts in conjugation with each other. This inter-dependence of sources calls for a detailed scientific analysis of all the sources that are in play. Waste management facilities have already been established as a significant contributor of microplastics to the aquatic and terrestrial environment. A systematic overview of the scientific literature reveals that the existing body of scientific knowledge is mainly focused on wastewater treatment facilities as a source/pathway of microplastics in the environment. Recently the focus shifted towards solid waste management facilities through landfills. Poor plastic waste management practices made discarded plastics the most dominant component of solid wastes. This review elucidates the occurrence and distribution of microplastics, characteristics of microplastics, including size, shapes, colors, and polymer types, in leachate and refuse of landfills. Furthermore, we discussed the transport mechanisms and pathways used by microplastic present in landfills to migrate to subsurface or groundwater and adjacent aquatic bodies. Last, based on the findings, we summarized the gaps in existing studies and suggested future perspectives to be focused on the future. The abundance of microplastics is attributed to the volume of plastic waste in landfills, management of leachate originating from landfills, application of leachate, and age of landfills. Microplastics abundance and characteristics vary in leachate and refuse. Smaller microplastics are predominant in leachate while larger microplastics are predominant in refuse. Landfills are capable of generating secondary microplastics from fragmentation and degradation. Further studies on microplastics in landfills are necessa